Peran Pemimpin Adat dalam Membangun Komunitas yang Harmonis dan Mempertahankan Warisan Budaya - Masniar Masniar; Debi Servinta BR Perangin – Angin; Wildansyah Lubis; Winara Winara (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This article discusses the strategic role of traditional leaders in building harmonious communities while preserving cultural heritage. Amidst the challenges of globalization, traditional leaders serve as guardians of tradition and motivators in educating the younger generation about their cultural values. Through various community activities, traditional leaders create spaces for dialogue that strengthen social ties and cooperation among community members. In addition, they also act as mediators in resolving conflicts, using local wisdom-based approaches to achieve peaceful solutions. Thus, this article highlights the importance of traditional leadership in creating social harmony and preserving cultural identity in the modern era.